2018
DOI: 10.5812/hepatmon.84182
|View full text |Cite
|
Sign up to set email alerts
|

Liver Fibrosis is Associated with NAFLD Activity Score in Chronic Hepatitis B Patients with Liver Steatosis

Abstract: Background: Chronic hepatitis B (CHB) and non-alcoholic fatty liver disease (NAFLD) are two leading hepatic diseases that cause severe public health problems. The relationship between the severity of NAFLD and liver fibrosis in CHB patients remains controversial.Objectives: This study aimed at further clarifying the association between them. Methods: A total of 272 CHB patients and 31 NAFLD patients without CHB, who underwent liver biopsies and routine blood tests were included. The NAFLD activity scores (NAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…In our study, we excluded 5 studies that did not provide time-to-event data. [41][42][43][44][45] Second, Mao et al 39 included a recent administrative database study with 48,335 CHB patients reported a higher risk of HCC and death in CHB-FL group, which is contrasting to our findings. 19 However, this study included both hepatitis B and C patients, and subgroup analysis of CHB patients did not provide time-to-event data to be included in our study and did not provide details on which factors were being adjusted for.…”
Section: Discussioncontrasting
confidence: 98%
“…In our study, we excluded 5 studies that did not provide time-to-event data. [41][42][43][44][45] Second, Mao et al 39 included a recent administrative database study with 48,335 CHB patients reported a higher risk of HCC and death in CHB-FL group, which is contrasting to our findings. 19 However, this study included both hepatitis B and C patients, and subgroup analysis of CHB patients did not provide time-to-event data to be included in our study and did not provide details on which factors were being adjusted for.…”
Section: Discussioncontrasting
confidence: 98%
“…After removing duplicates and screening the titles and abstracts, 135 potentially available studies were identified. Of these, 34 eligible studies7–10,13–42 were included for analysis at the final stage.…”
Section: Resultsmentioning
confidence: 99%
“…In a population-based cohort study in Turkey, liver fibrosis was emphasized as one of the serious complications hepatitis B (16). Another study linked the prevalence of liver fibrosis to the severity of non-alcoholic fatty liver disease in CHB patients (17). The elderly and diabetic people were found more likely to have serious hepatitis B complications, such as HCC (18).…”
Section: Physical Challengesmentioning
confidence: 99%